PATTERNS OF CODESWITCHING IN JAVANESE CULTURE ONLINE FORUM - Nursanti, Emi (Widyaparwa, 2024)
This study specifically aims at 1) finding and interpreting the frequencies of the interrelation between the codeswitching types and functions, and 2) describing the communication features of a Javanese culture online forum based on the codeswitching patterns.  By using a mixed-method design, this study used qualitative data to explain the quantitative results. The data were multilingual utterances in a webinar. The study found that 1) some frequent codeswitching patterns occur in the webinar are: insertion-referential (40.4%), tag-expressive (20.1%), congruent lexicalization-referential (18.0%), congruent lexicalization-expressive (9.5%), intersentential-directive (2.8%), insertion-metalingual (2.1%), congruent lexicalization-metalingual (1.8%), insertion-directive (0.5%), insertion-expressive (0.5%), alternation-expressive (0.3%), congruent lexicalization-phatic (0.3%), and tag-phatic (0.2%). 2) Those patterns suit the nature of the events and the sociocultural background of the people involved. The dominant employment of cultural terms with no equivalent translations and the hierarchical and non-egalitarian Javanese society were the factors motivating the dominant occurrence of the referential and expressive functions of codeswitching.Kajian ini secara spesifik bertujuan untuk 1) menemukan dan menginterpretasikan frekuensi interelasi antara jenis dan fungsi alih kode, dan 2) mendeskripsikan fitur komunikasi forum daring kebudayaan Jawa berdasarkan pola alih kode tersebut. Dengan desain metode campuran, penelitian ini menggunakan data kualitatif untuk menjelaskan hasil kuantitatif. Datanya adalah ujaran multibahasa dalam sebuah webinar. Hasil penelitian menemukan bahwa 1) beberapa pola alih kode yang sering terjadi adalah: insertion-reference (40.4%), tag-expressive (20.1%), congruent lexicalization-reference (18.0%), congruent lexicalization-expressive (9.5%), intersentential-directive (2.8%), insertion-metalingual (2.1%), congruent lexicalization-metalingual (1.8%), insertion-directive (0.5%), insertion-expressive (0.5%), alternation expressive (0.3%), congruent lexicalization-phatic (0.3%), dan tag-phatic (0.2%). 2) Pola tersebut sesuai dengan karakter peristiwa tutur dan latar belakang sosial budaya masyarakat yang terlibat. Penggunaan istilah-istilah budaya yang dominan tanpa terjemahan yang setara dan masyarakat Jawa yang hirarkis dan non-egaliter menjadi faktor-faktor yang melatarbelakangi munculnya fungsi alih kode referensial dan ekspresif yang dominan.